Baitul Hikmah Pusat Keemasan Ilmu Pengetahuan Dinasti Abbasiyah - Diyah Andini Kusumastuti; Abdul Khobir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Islamic Abbasid Dynasty experienced progress in the field of Education which was advanced, solid, complete and well integrated supported by an adequate education system at that time. Baitul Hikmah which became the center of scientific development, especially mathematics (Al-Khwarizmi), astronomy (Al-Biruni), and medicine (Ibn Sina) which became an intellectual center and packaging period during the Abbasid Dynasty. This study uses a systematic literature review research method with a qualitative descriptive research approach through literature review or literature studies, journals, articles, and books that discuss Baitul Hikmah during the Abbasid Dynasty. The results of this study show that Baitul Hikmah was a library and translation center during the Abbasid Dynasty located in Baghdad. In addition, Baitul Hikmah has a considerable role in developing Islamic civilization, even at that time Islam experienced its heyday